2021
DOI: 10.3389/fphar.2021.622774
|View full text |Cite
|
Sign up to set email alerts
|

Ang II Promotes Cardiac Autophagy and Hypertrophy via Orai1/STIM1

Abstract: The pathophysiology of cardiac hypertrophy is complex and multifactorial. Both the store-operated Ca2+ entry (SOCE) and excessive autophagy are the major causative factors for pathological cardiac hypertrophy. However, it is unclear whether these two causative factors are interdependent. In this study, we examined the functional role of SOCE and Orai1 in angiotensin II (Ang II)-induced autophagy and hypertrophy using in vitro neonatal rat cardiomyocytes (NRCMs) and in vivo mouse model, respectively. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In contrast, with these studies, other studies have suggested that STIM1/Orai1 stimulates autophagy [64][65][66]. In cardiomyocyte, the silencing of Orai1 could markedly attenuate the Ang II-induced LC3-II accumulation and inhibited autophagy both in vitro and in vivo [64]. It seems that the autophagy-related role of Orai1 and SOCE can be either stimulating or inhibiting depending on the cell type or the stimulation it receives.…”
Section: Transient Receptor Potential Canonical and Orai1 Channelsmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, with these studies, other studies have suggested that STIM1/Orai1 stimulates autophagy [64][65][66]. In cardiomyocyte, the silencing of Orai1 could markedly attenuate the Ang II-induced LC3-II accumulation and inhibited autophagy both in vitro and in vivo [64]. It seems that the autophagy-related role of Orai1 and SOCE can be either stimulating or inhibiting depending on the cell type or the stimulation it receives.…”
Section: Transient Receptor Potential Canonical and Orai1 Channelsmentioning
confidence: 73%
“…Another group showed that the knockdown of Orai1 enhances the 5-fluorouracil (5-FU)-induced inhibition of the phosphoinositide 3-kinase-AKT-mTOR pathway and potentiated 5-FU activated autophagic cell death in hepatocarcinoma cells [63]. In contrast, with these studies, other studies have suggested that STIM1/Orai1 stimulates autophagy [64][65][66]. In cardiomyocyte, the silencing of Orai1 could markedly attenuate the Ang II-induced LC3-II accumulation and inhibited autophagy both in vitro and in vivo [64].…”
Section: Transient Receptor Potential Canonical and Orai1 Channelsmentioning
confidence: 97%
“…Various preclinical studies documented that AngII mediates myocardial structural protein alterations, such as the overexpression of the β isoform of the myosin heavy chain (MHC) and the skeleton actin protein as well as cardiac fibrosis through the JMJD1C/TIMP 1 [44] and FOXF1/TGFβ 1/SMAD3 [45] signaling pathways as well as the involvement of the CD38/SIRT3 (Sirtuin)-FOXO3, Ca 2+ -calcineurin-NFAT (nuclear factor of activated T cells) [46], and TNFα/NFkB/CD44 signaling pathways [47]. In addition, AngII induces the upregulation of autophagy to mediate its cardiac pathogenesis through the activation of SOCE (store operated Ca 2+ entry)/Orai1 (a pore forming subunit for calcium permeation)/STIM1(Ca 2+ sensor) [48] and the inhibition of mammalian sterile 20-like kinase 1 (Mst1), a mediator of the Hippo signaling pathway [49]. In an experimental animal model of heart failure, it was documented that AngII decreased the levels of circulating IGF1 and elevated IGF1 and the expression of its specific receptor in the cardiac muscles [50].…”
Section: Angiotensin Ii-induced Cardiac Dysfunction Mimics Cardiac Ca...mentioning
confidence: 99%
“…Angiotensin II (Ang II), a bioactive octa-peptide, is the representative hormone in RAS. Accumulating evidence shows that Ang II contributes to pathological cardiac hypertrophy and the resultant heart failure, indirectly via increased blood pressure and/or directly acting on cardiomyocytes [ 3–5 ].…”
Section: Introductionmentioning
confidence: 99%